Eficiência agroeconômica e aspectos fisiológicos no consórcio de rúcula (Eruca sativa Miller) com espécies condimentares - Viana, Caris dos Santos (2017)
Consortium cultivation is a promising technique for vegetables, as it improves the use of space and thus increases productivity per unit area. Despite the positive effect for the producer, this system is considered complex, being necessary the knowledge of the interaction of the plants that will coexist so that its indication can be effected. In this sense, the general objective of this work was to evaluate the productive efficiency and the physiological behavior of arugula plants intercropped with aromatic and spice species. The study was conducted at the Didactic Horta of the Federal University of Ceará, in a randomized block design, with four replications and seven treatments: T1 (single cultivation of arugula), T2 (intercropped cultivar arugula and coriander), T3 ), T4 (intercropped cultivar arugula and Nira), T5 (single coriander cultivation), T6 (single parsley cultivation) and T7 (single crop of Nira). Plant breeding evaluations related to productivity, economic efficiency, physiological behavior and competitive ability of arugula were carried out. The consortium of arugula and coriander was the combination of species that presented the best agronomic performance. For the physiological characteristics evaluated, no differences were observed between the single cultivation of arugula and its consortia, however, for the leaf area and leaf area index, the highest values were observed for the arugula and coriander consortium. From the cultures used in the consortium with the arugula, coriander was the one with the highest index of aggressiveness, competition ratio and compensation ratio. It is concluded with this work that the arugula and coriander consortium allows greater economic returns to the producer.